Histidine-tryptophan-ketoglutarate solution decreases mortality and morbidity in high-risk patients with severe pulmonary arterial hypertension associated with complex congenital heart disease: an 11-year experience from a single institution - Li,X.W. (2016)
Cardioplegic reperfusion during a long term ischemic period interrupts cardiac surgery and also increases cellular edema due to repeated solution administration. We reviewed the clinical experiences on myocardial protection of a single perfusion with histidine-tryptophan-ketoglutarate (HTK) for high-risk patients with severe pulmonary arterial hypertension associated with complex congenital heart disease. This retrospective study included 101 high-risk patients undergoing arterial switch operation between March 2001 and July 2012. We divided the cohort into two groups: HTK group, myocardial protection was carried out with one single perfusion with HTK solution; and St group, myocardial protection with conventional St. Thomas' crystalloid cardioplegic solution. The duration of cardiopulmonary bypass did not differ between the two groups. The mortality, morbidity, ICU stay, post-operative hospitalization time, and number of transfusions in HTK group were lower than those in St group (P<0.05). Univariate and multivariate analysis showed that HTK is a statistically significant independent predictor of decreased early mortality and morbidity (P<0.05). In conclusion, HTK solution seems to be an effective and safe alternative to St. Thomas' solution for cardioplegic reperfusion in high-risk patients with complex congenital heart disease.